Leadership distributed among postgraduate students who work in educational institutions in vulnerable contexts - Aldoradin Rodríguez, Athena Bertha (2019)
Distributed leadership is a transactional approach of institutional management that has evolved to the conception of an interactive management between the director and the teaching staff, without reporting current evidences of its functionality in vulnerable contexts. Because of this, the research proposed to establish differences in the context of vulnerability, gender, academic degree, postgraduate training, and years of work. It was developed through a comparative -descriptive transectional design, in asample of 154 teachers from public educational institutions, grouped according to the context (vulnerable = 86, not vulnerable = 68) from the city of Callao (Peru), for which purpose the Multifactorial Leadership Distributed Questionnaire was used. The analysis made it possible toconclude that teachers fromvulnerable contexts, with less time working in educational institutions, and with constant training (masters or doctorate courses), can distribute leadership to a greater extent than teachers with moreyears in the public career (appointed or hired), without constant training. Gender is not a differentiator of this type of leadership. Finally, it is necessary to find new contextual differences, according to the level of attachment of the teacher towardshis managers in the management with low resources.